Late-life changes in ethnoracial self-identification: evidence from Social Security administrative data - Breen, CF (Springer, 2023)
Researchers generally recognize that ethnoracial identification may shift over the life course. However, the prevalence of these shifts across cohorts and among older adults remains open questions. Using administrative data from Social Security applications from 1984 to 2007, we quantify the magnitude and direction of later-life shifts in ethnoracial self-identification between Black, White, Asian, American Indian, and Hispanic categories for the “Greatest Generation,” those born between 1901 and 1927. Overall, 2.3% of persons in these data changed their ethnoracial identification after the age of 57, with distinct patterns of change for ethnoracial subgroups. By linking to the 1940 Census, we find a positive and significant association between socioeconomic status in early life and a shift from non-White to non-Hispanic White identification in later life. We conclude that ethnoracial self-identification fluidity continues even among older adults, varying in response to social position, ethnoracial climate, and events in greater society.